Engeletin Alleviates the Inflammation and Apoptosis in Intervertebral Disc Degeneration via Inhibiting the NF-κB and MAPK Pathways - Li B; Yang X; Zhang P; Guo J; Rong K; Wang X; Cao X; Zhou T; Zhao J (Dove Medical Press, 2022)
Baixing Li,* Xiao Yang,* Pu Zhang, Jiadong Guo, Kewei Rong, Xin Wang, Xiankun Cao, Tangjun Zhou, Jie Zhao Shanghai Key Laboratory of Orthopedic Implants, Department of Orthopedics, Ninth People's Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, 200011, People's Republic of China*These authors contributed equally to this workCorrespondence: Tangjun Zhou; Jie Zhao, Shanghai Key Laboratory of Orthopedic Implants, Department of Orthopedics, Ninth People's Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, 200011, People's Republic of China, Tel +8621-23271159, Fax +8621-63139920, Email zhoutangjun@outlook.com; profzhaojie@126.comPurpose: Low back pain (LBP) induced by intervertebral disc degeneration (IDD) brings progressively painful status and impairs the normal daily living. Engeletin is a plant-derived medicine with anti-inflammation and antioxidant functions. Therefore, we aim to confirm its protective effects against the intervertebral disc degeneration in vivo and in vitro.Methods: The cytotoxicity of engeletin was validated by CCK-8 tests. Using the TNF-α to simulate the inflammation status in vitro, the expression of inflammatory mediators and MMP families were determined by qPCR, Western blotting and confocal microscopy. Cell apoptosis was analyzed by flow cytometry and TUNEL assay. The expression of apoptosis-related proteins was tested by Western blotting. The activation of NF-κB and MAPK pathways was evaluated by Western blotting and confocal microscopy. In vivo, percutaneous needle puncture was used to establish the IDD model in rat, and engeletin was administrated via intradiscal injection. The therapeutic effects of engeletin were detected through imaging and histology analysis.Results: Cell viability tests demonstrated there was little cytotoxicity of engeletin toward NP cells. Pretreatment with engeletin effectively ameliorate the TNF-α-induced up-regulation of inflammatory mediators and MMP families, promoting the anabolism of ECM meanwhile. Cell apoptosis was also attenuated with the addition of engeletin. We found that the activation of MAPK and NF-κB signaling pathways and the nuclear translocation of phosphorylated p65 and p38 were inhibited prominently with the treatment of engeletin which may be the potential molecular mechanism for its anti-inflammation effects. Finally, the IDD induced by percutaneous needle puncture was partially alleviated with the injection of engeletin in vivo.Conclusion: As a natural compound with little cytotoxicity, engeletin possesses the outstanding anti-inflammation and anti-apoptosis effects in the process of IDD in vitro and in vivo, which may be a promising medicine for the prevention and treatment of IDD-related low back pain.Keywards: intervertebral disc degeneration, engeletin, nucleus pulposus, inflammation, apoptosis, NF-κB and MAPK signaling pathways